Urgensi Makna Kontekstual (Dalālah Siyāqiyyah) dan Teori Kontekstual (Naẓariyyah al-Siyāq) dalam Penelitian Semantik: The Urgency of Contextual Meaning (Dalālah Siyāqiyyah) and Contextual Theory (Naẓariyyah al-Siyāq) in Semantic Research - Mohammad Yusuf Setyawan (Universitas Ahmad Dahlan, 2022)
This article aims to reveal the urgency of contextual meaning (dalālah siyāqiyyah) and contextual theory (naẓariyyah al-siyāq) in Arabic semantic research. The study of contextual meaning is important to reveal because lexical meaning is not sufficient to understand an utterance or text. This research is library research that uses a qualitative descriptive method. The results of the study indicate that context is an element of the meaning referred to in the structure of the text or speech because the context does not only pay attention to words and sentences but also to written and spoken texts and the whole through the relationship between vocabularies in a context. Contextual theory in semantic research is very useful in revealing the contextual meaning of an utterance. The contextual theory does not pay attention to the types of context except the context of language or context of pronunciation so this theory explains a collection of words that are neatly arranged with the word that is the object of study. This theory also focuses on explaining the syntactic and morphological characteristics of an utterance.